ENPROSALT (Energy Produce by Salt) / Nurqistina Batrisyia Md Nirwan ... [et al.] - Md Nirwan, Nurqistina Batrisyia; Azhar, Rabiatul Adawiyah; Zakaria, Nur Hamizah; Engku Abdul Malik, Engku Shifaa Nur Sahira; Ahmad Jefri, Nurul Sofea Balqis; Amir, Khairul Anwar (2021)
Most of us use dry cells for electronic devices. When the battery is losing its power, users will continue to just throw it away. Not many people know the methods of disposing of batteries properly after the battery runs out of power. Most of us usually tossed the batteries into the dustbin. Crucially, improper disposal of batteries causes plumbum toxic leak which lead to pollution being spread widely. When it enters the human body, it becomes toxic in our body and causes adverse health effects. Based on awareness, we want to create a new product towards Green Technology as an alternative called ENPROSALT as a new energy to replace the existing products. Salt cells are capable of replacing dry cells battery by producing and generating high voltage power and lasts longer. In a study that was conducted, the salt cells with a solution of certain concentration were going through the process of electrolysis. In these experiments, salt cells use two pieces of metal copper and aluminum in the electrolysis process and salt as the electrolyte. The result is electrical current can be generated. The use of the salts cell is very easy because it only requires a certain concentration of salt water connected to two electrodes. By placing the two metal sheets which represents the anode and cathode, then connected to the wires, therefore LED lights will light up. With the creation of this innovative product, we can reduce the pollution caused by improper disposal of dry cells batteries and thus makes ENPROSALT as a source of alternative energy.